2022
DOI: 10.3899/jrheum.210974
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Signal and Bone Erosions at the Enthesis Are Independently Associated With Ultrasound Joint Erosive Damage in Psoriatic Arthritis

Abstract: Objective To explore the association of the OMERACT ultrasound (US) entheseal abnormalities with the presence of US joint bone erosions in psoriatic arthritis (PsA). Methods Consecutive PsA patients were included in this cross-sectional study. Demographic and clinical parameters were collected. A bilateral US assessment was carried out at the following entheses: plantar fascia, quadriceps, patellar (proximal and distal) and Achilles tendons. The following US entheseal abnormalities were registered: hypoechogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The results of Smerilli et al 12 are also consistent with the results obtained by other authors, who point out that the enthesis PD is the main US lesion for enthesis evaluation in SpA and PsA, 14 even suggesting that it is sufficient to define enthesitis not only as an isolated elemental lesion. 15 In their cohort of patients with PsA, Smerilli et al 12 found PD present in 55.8% of patients and 10.6% of entheses, similar to previous findings (66.7% of patients and 10.2% of entheses), 16 although a proper comparison seems complex due to the different selection of explored entheses and disease activity states of the included patients. Another series also reported high percentages of enthesis PD (81.5-96%), [16][17][18] and Mease et al 19 proposed that the enthesis domain could be associated with greater PsA disease activity, globally supporting the association between the enthesis domain (highlighted by PD) and the systemic activity in SpA and PsA, thereby emphasizing the importance of introducing new methods to improve the evaluation of entheses.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…The results of Smerilli et al 12 are also consistent with the results obtained by other authors, who point out that the enthesis PD is the main US lesion for enthesis evaluation in SpA and PsA, 14 even suggesting that it is sufficient to define enthesitis not only as an isolated elemental lesion. 15 In their cohort of patients with PsA, Smerilli et al 12 found PD present in 55.8% of patients and 10.6% of entheses, similar to previous findings (66.7% of patients and 10.2% of entheses), 16 although a proper comparison seems complex due to the different selection of explored entheses and disease activity states of the included patients. Another series also reported high percentages of enthesis PD (81.5-96%), [16][17][18] and Mease et al 19 proposed that the enthesis domain could be associated with greater PsA disease activity, globally supporting the association between the enthesis domain (highlighted by PD) and the systemic activity in SpA and PsA, thereby emphasizing the importance of introducing new methods to improve the evaluation of entheses.…”
supporting
confidence: 85%
“…In this study, 12 joint erosions were found to be associated in the univariate and multi-variate model and in the logistic regression analysis with enthesis PD (β 0.51, P < 0.001 and odds ratio [OR] 1.74, 95% CI 1.17-2.59, P < 0.01), enthesis erosion (β 0.20, P = 0.02 and OR 3.17, 95% CI 1.30-7.77, P = 0.01), and greyscale joint synovitis (β 0.42, P = 0.03 and OR 2.59, 95% CI 1.16-5.78, P = 0.02). The results of Smerilli et al 12 are also consistent with the results obtained by other authors, who point out that the enthesis PD is the main US lesion for enthesis evaluation in SpA and PsA, 14 even suggesting that it is sufficient to define enthesitis not only as an isolated elemental lesion. 15 In their cohort of patients with PsA, Smerilli et al 12 found PD present in 55.8% of patients and 10.6% of entheses, similar to previous findings (66.7% of patients and 10.2% of entheses), 16 although a proper comparison seems complex due to the different selection of explored entheses and disease activity states of the included patients.…”
mentioning
confidence: 81%
See 3 more Smart Citations